How geomagnetic storms affect the loss of Starlink satellites in February 2022? - Nizam Ahmad; La Ode Muhammad Musafar Kilowasid; Hanif Fakhrurroja; Neflia; Abdul Rachman; Asnawi Husin; Haries Fathoni (Earth, Planets and Space)
Abstract On February 8, 2022, approximately 40 of the 49 Starlink satellites were reported to have lost altitude, leading to atmospheric re-entry. SpaceX reported that the orbital decay on Starlink satellites was considered to be linked to a geomagnetic storm that was initiated on February 3, 2022. We attempted to analyze the cause of orbital decay by sampling all Starlink satellites registered in the SpaceTrack database and then tracing some space weather parameters and species density variations in the thermospheric layer. We employed the solar wind and IMF Bz to see their impact on geomagnetic activity. Moreover, we also analyzed the electric field Ey, Dst, AE, and Ap indices in addition to the solar EUV flux to see their impact on the Starlink satellite environment. We discovered three geomagnetic substorms during the analysis period: two successive substorms on February 4 and 5, and one additional substorm on February 10. We inferred that magnetic substroms significantly affected species densities, mainly O, O2, and N2, around some Starlink satellites, leading to an increase in atmospheric drag. There was a time delay between the substorms and orbital decay on Starlink satellites. However, some Starlink satellites were not affected by geomagnetic substorms due to insignificant changes in their environment. The reason for this is that, despite having lower altitudes, all decaying Starlinks were located in the midnight-dawn sector, in which the drift of ionospheric currents was predominantly driven by westward electrojets. On the other hand, all non-decaying Starlink satellites that had higher altitudes resided in the dusk–midnight sector of magnetic local time, where the impact of substorms insignificantly affected their altitudes. Graphical Abstract